Sensitivity Analysis of the Realized Risks of Auditing with Uncertainty Concerning Internal Control Evaluations - Smieliauskas, Wally (Journal of Accounting Research, 1985)
Auditing, Internal control evaluation, Audit risk, Substantive testing